Tinjauan Fiqh Siyasah terhadap Penolakan Judicial Review Pasal 222 Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum Oleh Mahkamah Konstitusi - Fayza Ayu Wulandari; Yufi Wiyos Rini Masykuroh; Ahmad Fauzi Furqon (Lembaga Pengembangan Kinerja Dosen, 2024)
Judicial reviews on the presidential and vice-presidential nomination threshold in Article 222 of Law No. 7/2017 on General Elections have been repeatedly rejected by the Constitutional Court. It has become a public debate and is seen as contrary to academic reasoning because it is not in line with the logic of democracy. Rules that are considered detrimental to the community and political parties in the election of the head of state. Accordingly, the study of fiqh siyasah clarifies the prerequisites for the election system and the selection of the imam (caliph). The purpose of this study is to find out how the legal considerations by the Constitutional Court rejected the judicial review in Article 222 and to find out what the views of Islamic jurisprudence are on the presidential and vice-presidential nomination threshold rules in general elections. The author of this work employs normative legal research methodologies in addressing relevant research, drawing on legislation, journal articles, books, and other sources. This study concludes by using 4 decisions that were rejected by the constitutional court, namely in decisions 53/puu-xv/2017, 49/puu-xvi/2018, 54/puu-xvi/2018 and decision number 73/puu-xx/2022. The considerations of the court stated that the decision related to the presidential threshold was constitutional and still applicable. That the article being tested is considered contrary to the constitution, especially Article 6A of the 1945 Constitution with the argument that the petitioners cannot change the Constitutional Court's stance on all decisions. Meanwhile, in the view of fiqh siyasah does not recognize how the provisions of the vote threshold for the election of an imam.